PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA CABANG PT. BNI, Tbk. KOTA MEDAN - Yovie Ernanda; Sari Susanti Simamora; Araventa Siolina Br Sembiring Meliala; Herry Ivan Nathanael Sitompul; Sri Fatmawati (Idaarah: Jurnal Manajemen Pendidikan, 2020)
This study aims to see how the work environment influences, work motivation on the performance of the bank employees. The influential subjects in this study were the bank employees with 70 respondents. By collecting interview data, distributing questionnaires, as well as literature study which is also equipped with related tests, namely: validity tests, reliability tests, hypothesis test, and coefficient of determination. And calculated using SPSS 23 aims to get accurate results in order to draw conclusions whether this influence is a positive or negative influence on employee performance at the branch of PT BNI, Tbk. Medan. So it can be concluded that the work environment with work motivation does or does not significantly affect the performance of  employees at branch of PT BNI, Tbk. Medan.